2017
DOI: 10.1177/1056492617718089
|View full text |Cite
|
Sign up to set email alerts
|

(Engaging or Avoiding) Change Through Reflexive Practices

Abstract: In this paper, we explore the ways in which individuals deploy reflexive practices in order to avoid or engage with a call to change either oneself or the social context. We begin by developing a categorization of the modes of reflexive practice associated with avoidance or engagement. We go on to develop -through a relationally reflexive research process -three contributions that build on this. First, we build an understanding of what a repertoire of reflexive practices may include, and 'what is going on' in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 66 publications
(224 reference statements)
1
55
0
4
Order By: Relevance
“…As noted earlier there is a variety of research that notes the emotional aspects of the research process from the viewpoint of the organizational researcher (Evans et al, 2017;Whiteman et al, 2009), but here the focus upon the emotions of the researched enables us to identify issues and events that are particularly pertinent to our participants, that are entangled within participant reflexivity processes. As Hibbert et al (2017) note, and as we have also identified in our own participants, this may signify a call to change that can lead to participants changing their behaviours, or at least re-evaluating what they are currently doing. Not only does this signal an issue or event worthy of further exploration, but we would argue that the researcher also has some level of responsibility here to permit participants to explore and develop their reflexivity and emotions at such pivot points in a safe space (Hibbert and Cunliffe, 2015).…”
Section: What Is the Added Value For Researchers In Accessing Particimentioning
confidence: 70%
See 4 more Smart Citations
“…As noted earlier there is a variety of research that notes the emotional aspects of the research process from the viewpoint of the organizational researcher (Evans et al, 2017;Whiteman et al, 2009), but here the focus upon the emotions of the researched enables us to identify issues and events that are particularly pertinent to our participants, that are entangled within participant reflexivity processes. As Hibbert et al (2017) note, and as we have also identified in our own participants, this may signify a call to change that can lead to participants changing their behaviours, or at least re-evaluating what they are currently doing. Not only does this signal an issue or event worthy of further exploration, but we would argue that the researcher also has some level of responsibility here to permit participants to explore and develop their reflexivity and emotions at such pivot points in a safe space (Hibbert and Cunliffe, 2015).…”
Section: What Is the Added Value For Researchers In Accessing Particimentioning
confidence: 70%
“…Perhaps it is not a surprise therefore that some of our participants suggested that the opportunity for reflexive critique led to them planning or activating behavioural changes. This link between reflexivity and action demonstrates how as Hibbert et al, (2017) suggest, reflexive practice can lead to a call for action. In line with their suggestion, it is the combination of the emotional experiences and reflexive practices that will impact upon whether a call to action is either mobilized or constrained.…”
Section: Study Descriptionmentioning
confidence: 83%
See 3 more Smart Citations